PENINGKATAN KESEJAHTERAAN EKONOMI MASYARAKAT MELALUI PEMBENTUKAN KELOMPOK USAHA BERSAMA KERAJINAN “INKA” DI DESA TAMAN SARI KECAMATAN GUNUNG SARI KABUPATEN LOMBOK BARAT - Ni Luh Putu Anom Pancawati; I Made Ngurah Oka Mahardika; I Made Sudarma (Nusantara Hasana Journal, 2021)
Banjar Rojong Dusun Rendang Bajur Taman Sari Village, Gunung Sari District, West Lombok Regency has the potential of resources in the form of coconut trees that are available quite abundantly and is one of the areas producing woven craft center woven lidi "inka". But that potential is not balanced with the creativity of the community in managing it, instead encountered several obstacles, one of which is still working individually to utilize the potential for raw material resources. Especially during the COVID-19 pandemic has an impact on the uncertainty of their income and well-being.  As one of the efforts to overcome the problem is to provide knowledge and information to the community and the formation of joint business groups through community service activities. This service is carried out in collaboration between community service teams consisting of lecturers and students with the community. This devotional activity consists of program preparation, program implementation and the establishment of joint business groups as an output of the implementation of community service. The majority of the inka crafter who are the womens are very enthusiastic and excited about the implementation of this devotion program. With the establishment of a joint business group, the "inka" crafter will more easily manage the productivity of its woven products and gain easy access to the application of capital assistance to related parties.